2009
DOI: 10.1029/2008ja013707
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polar cap patches and field‐aligned irregularities as observed with an all‐sky airglow imager at Resolute Bay and the PolarDARN radar at Rankin Inlet

Abstract: [1] Simultaneous two-dimensional observations of airglow enhancement and radar backscatter from field-aligned irregularities (FAIs) associated with polar cap patches were conducted. The spatial structure of 630 nm airglow from polar cap patches was imaged using an all-sky airglow imager at Resolute Bay, Canada, while backscatter echoes from decameter-scale FAIs were observed using the newly constructed HF Polar Dual Auroral Radar Network (PolarDARN) radar at Rankin Inlet, Canada. Both the airglow enhancement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 36 publications
2
70
1
Order By: Relevance
“…The present model cannot replicate this result as it does not consider structures of arbitrary shapes. The observed patches are often irregularly shaped, which could result in a limited number of places along their edges where the relative gradient/plasma drift orientation is such that no growth would occur (Hosokawa et al, 2009). In this way, these observations are not necessarily inconsistent with the results presented here, but they cannot be represented by the model in its current form.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The present model cannot replicate this result as it does not consider structures of arbitrary shapes. The observed patches are often irregularly shaped, which could result in a limited number of places along their edges where the relative gradient/plasma drift orientation is such that no growth would occur (Hosokawa et al, 2009). In this way, these observations are not necessarily inconsistent with the results presented here, but they cannot be represented by the model in its current form.…”
Section: Discussioncontrasting
confidence: 54%
“…Greater power from radar backscatter is indicative of more decameter-scale structuring, which agrees with a greater growth rate on the trailing edge. Some studies have shown that radar backscatter (and presumably plasma structuring) occurs within the entire volume of polar patches (Hosokawa et al, 2009). The present model cannot replicate this result as it does not consider structures of arbitrary shapes.…”
Section: Discussionmentioning
confidence: 99%
“…3g and 3h), significant scintillations were also found. Very weak or no scintillations occurred during the pass of patch A at around 19:00 UT, which implies that not all polar cap patches have become structured during their passage across the polar cap (Hosokawa et al 2009). However, after a long travel in the polar cap, most of the patches have become structured.…”
Section: Discussionmentioning
confidence: 99%
“…The imager at Resolute Bay, Canada (74.73°N, 265.07°E; AACGM latitude 82.9°) has been in operation since January 2005 as a part of the OMTIs system [Hosokawa et al, 2006]. This imager has a number of optical filters, such as 557.7 nm, 630.0 nm, 777.4 nm, Na-line, and OH-band; this enables us to study various upper atmospheric phenomena occurring in the polar cap region, such as polar cap patches [Hosokawa et al, 2006[Hosokawa et al, , 2009a[Hosokawa et al, , 2009b[Hosokawa et al, , 2010a, tongue of ionization [Hosokawa et al, 2009c[Hosokawa et al, , 2010b, polar cap aurora [Koustov et al, 2008;Jayachandran et al, 2009], and gravity waves at mesospheric heights [Suzuki et al, 2009].…”
Section: Instrumentationmentioning
confidence: 99%